P-009 Twisting: an intraprocedural challenge with pipeline deployment, increased with the second-generation, flex device. (22nd July 2018) - Young, R; Bender, M; Campos, J; Jiang, B; Zarrin, D; Vo, C; Caplan, J; Huang, J; Tamargo, R; Lin, L; Colby, G; Coon, A
Abstract : Introduction: Pipeline Embolization Device 'twisting' manifests with appearance of a 'figure 8' in perpendicular planes on DSA. We noticed increased frequency of twisting with the second-generation, PED-Flex device. Methods: Case images were reviewed for instances of twisting from a prospectively-maintained, IRB-approved database of patients undergoing flow diversion for cerebral aneurysm. Results: From 08/2011–02/2015, 367 PED-Classic were used in 276 cases in 239 patients. Five twists were observed in four patients (1.4%, 5/367). From 02/2015–01/2018, 628 PED-Flex were used in 510 procedures in 427 patients and 19 twists were observed in 16 patients (3.0%, 19/628) (p=0.10). Twisting is common in large, non-saccular aneurysms located along the carotid artery. In twisting cases across both device generations, the average aneurysm size was 18 mm (range 4–50 mm), morphology was fusiform or dissecting in 30% of cases, and aneurysm location was 16 ICA, 2 ACA, and 2 basilar. Larger diameter and longer devices showed a predisposition to twisting. Of the 24 twisted devices, 29.0% were 5.0 mm diameter and only 20% were less than 4.5 mm. The average length of a twisted device was 27.5 mm (range 14–35 mm). Of the four cases with PED-Classic twists, two were remediated successfully, one was removed and a second device placed without twisting, and one case was aborted after successive twisted devices were removed. Of the 19 PED-Flex twists, 13 were remediated and six were removed. Procedural success was achieved in 15/16 PED-Flex twisting cases and one procedure was aborted. Remediation maneuvers differed by device generation but included exchanging a neutral catheter, resheathing, wagging, and balloon angioplasty. Overall, two major complications (10%) were observed: one patient with giant fusiform ACA aneurysm in which PED-Classic twist was remediated experienced delayed SAH and died; one patient with mid-basilar aneurysm in which PED-Flex twist was remediated experienced perforator stroke (mRS 4) potentially related to incomplete device apposition. Occlusion outcomes for twisted devices were inferior to the overall PED population. With PED-Classic, 0/3 patients with successful PED implantation after twisting showed complete aneurysm occlusion and 2/3 were ultimately re-treated. For PED-Flex, follow-up DSA was available for 62.5% (10/16); complete occlusion was observed in 50% (4/8) at 12 months and 50% (5/10) at last follow-up. Conclusion: Twisting is a rare intra-procedural event, more common with PED-Flex (3.0%) than the PED-Classic (1.4%). Although remediable, a twist can lead to major complications and diminishes occlusion outcomes. Disclosures: R. Young: None. M. Bender: None. J. Campos: None. B. Jiang: None. D. Zarrin: None. C. Vo: None. J. Caplan: None. J. Huang: 6; C; Longeviti. R. Tamargo: None. L. Lin: 2; C; Medtronic. G. Colby: 1; C; Medtronic, Stryker Neurovascular. 2; C; MicroVention, Codman. A. Coon: 1; C; Stryker Neurovascular. 2; C; InNeuroCo, Stryker Neurovascular, Medtronic Neurovascular.